2018
DOI: 10.1111/nyas.13686
|View full text |Cite
|
Sign up to set email alerts
|

The function and failure of sensory predictions

Abstract: Humans and other primates are equipped with neural mechanisms that allow them to automatically make predictions about future events, facilitating processing of expected sensations and actions. Prediction-driven control and monitoring of perceptual and motor acts are vital to normal cognitive functioning. This review provides an overview of corollary discharge mechanisms involved in predictions across sensory modalities and discusses consequences of predictive coding for cognition and behavior. Converging evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 200 publications
(310 reference statements)
1
34
0
Order By: Relevance
“…The interactions of pathways that underlie the complex processes for decision and action are disrupted in psychosis (reviewed in [61]) and in anxiety disorders that affect emotional processing through the amygdala (e.g., [5]). Considerable evidence suggests disruption of corollary discharge mechanisms in schizophrenia, affecting the sense of agency and attribution of thoughts, desires, and actions to external sources (e.g., [62][63][64][65][66][67][68][69][70]). The thalamocortical motif that links the thalamus with high-order association prefrontal cortices is likely vulnerable to disruption along multiple dimensions, including the known deficits in eye movements in schizophrenia, as shown in computational studies [71].…”
Section: Plos Biologymentioning
confidence: 99%
“…The interactions of pathways that underlie the complex processes for decision and action are disrupted in psychosis (reviewed in [61]) and in anxiety disorders that affect emotional processing through the amygdala (e.g., [5]). Considerable evidence suggests disruption of corollary discharge mechanisms in schizophrenia, affecting the sense of agency and attribution of thoughts, desires, and actions to external sources (e.g., [62][63][64][65][66][67][68][69][70]). The thalamocortical motif that links the thalamus with high-order association prefrontal cortices is likely vulnerable to disruption along multiple dimensions, including the known deficits in eye movements in schizophrenia, as shown in computational studies [71].…”
Section: Plos Biologymentioning
confidence: 99%
“…For example, impaired ability to differentiate external from self-produced sensory events has been linked to neuropsychiatric symptoms in schizophrenia (Blakemore, Smith, Steel, Johnstone, & Frith, 2000;Lemaitre, Luyat, & Lafargue, 2016;Lindner, Thier, Kircher, Haarmeier, & Leube, 2005;Spering, Dias, Sanchez, Schütz, & Javitt, 2013). This important topic has been covered by recent reviews (Bansal, Ford, & Spering, 2018;Thakkar, Diwadkar, & Rolfs, 2017) and will not be discussed here. Instead, we will review the mechanisms underlying sensory regulation based on normally functioning predictions of sensory action consequences.…”
Section: Predicting Sensory Consequences Of Movementsmentioning
confidence: 99%
“…Perceptual alterations caused by sensorimotor conflicts of upper-limb movements have also been observed in sensory domains other than somatosensation. For instance, studies reported a change in loudness perception of self-generated tones (by a button press), compared to tones presented passively [22][23][24][25] , which was associated with attenuated neural responses [26][27][28][29][30] . Recent studies have demonstrated that such auditory-motor self-attenuation effects can also be obtained for more complex sounds, such as voices 31,32 .…”
Section: Introductionmentioning
confidence: 99%